Effect Use of Cricket Flour (Gryllus Sp) in The Ration on Body Weight Gain, Consumption Rations and Ratio Conversion of Balenggek Cock Chickens For 12 Weeks - Tusa’diyah, Halimah; Akbar, syahro ali; Sari, Rica Mega (Department of Agriculture, 2023)
This study aims to determine how using cricket flour in rations affects body weight gain, ration consumption, and ration conversion of Balenggek crowing chickens for 12 weeks. Completely Randomized Design (CRD) 4 (four) treatments and 4 (four) replications, with 3 AKB males per replication. Treatment consists of P0 = No use of 0% cricket flour, P1 = Use of 2% cricket flour, P2 = Use of 4% cricket flour, P3 = Use of 6% cricket flour. The parameters measured in this research are Body Weight Gain, Ration Consumption, and Ration Conversion. The research results showed that the average body weight gain ranged from 45.53 -70.24 gr/head/week, feed consumption 296.69 - 319.30 gr/head/ week, and ration conversion 4.63 - 6.51%. From the research results it can be concluded that the addition of cricket flour in the ration had a very significantly different effect (P<0.01) on body weight gain, ration consumption, and ration conversion of balenggek roosters for 12 weeks with the best treatment P3 (Use of 6% Cricket Flour ).